2004
DOI: 10.1039/b403305a
|View full text |Cite
|
Sign up to set email alerts
|

Micro magnetic stir-bar mixer integrated with parylene microfluidic channels

Abstract: Previously, we reported a micro magnetic stir-bar mixer driven by an external rotating magnetic field and its rapid mixing performance in polydimethyl-siloxane (PDMS) channels. The PDMS piece with embedded fluid channels were manually aligned to a glass substrate and assembled. In this paper, we report the fabrication and testing results of a micro magnetic stir-bar monolithically integrated in parylene surface-micromachined channels with improved design features, including small tolerance of the stir-bar to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
141
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(142 citation statements)
references
References 25 publications
0
141
0
1
Order By: Relevance
“…Passive micromixers 1, [8][9][10][11][12] do not require external energy but only depend on the structure of the channel, and the mixing mechanism relies entirely on molecular diffusion or chaotic advection. For achieving a high mixing efficiency, active micromixers usually utilize the disturbance induced by an external field, such as the electric field, [13][14][15][16] the acoustic field, [17][18][19][20] and the magnetic field, 21,22 etc. However, it is often difficult to fabricate active micromixers for their integration with complicated components that trigger external fields.…”
Section: Introductionmentioning
confidence: 99%
“…Passive micromixers 1, [8][9][10][11][12] do not require external energy but only depend on the structure of the channel, and the mixing mechanism relies entirely on molecular diffusion or chaotic advection. For achieving a high mixing efficiency, active micromixers usually utilize the disturbance induced by an external field, such as the electric field, [13][14][15][16] the acoustic field, [17][18][19][20] and the magnetic field, 21,22 etc. However, it is often difficult to fabricate active micromixers for their integration with complicated components that trigger external fields.…”
Section: Introductionmentioning
confidence: 99%
“…Gong and W. Wen Biomicrofluidics 3, 012007 ͑2009͒ et al 48 developed an acoustically driven mixer based on the acoustic microstreaming principle; Shilton et al 49 demonstrated increased efficiency in particle concentration/separation and in generating intense micromixing in microliter drops by using concentric circular and elliptical transducers to focus the wave͒, and magnetohydrodynamics ͑Ryu et al 50 fabricated a magnetic stir bar composed of a free rotating rotor to which was applied a rotating external magnetic field͒. A cross-stream active mixer represents a system in which the flow in the main microfluidic channel is perturbed by actively controlled side-channel flows.…”
Section: -6mentioning
confidence: 99%
“…In particular, microrobots on a chip have great advantages for the treatment of biological cells with high throughput, due to their high speed and high accuracy [3]. Several actuation methods of microrobots OPEN ACCESS have been proposed for microscale cell manipulation, such as optical tweezers [4,5], magnetic actuators [6,7] and bubble robots driven by optically induced thermocapillary flow [8]. In previous studies, we proposed magnetically driven micro-tools (MMTs) for on-chip cell manipulation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%